Kenya Devolution Working Paper Series : Summary Overview - Kenya School of Government; World Bank (World Bank Group, Washington, DC, 2015)
Kenya has embarked on a highly ambitious decentralization that seeks to fundamentally change the relationship between government and citizens under the 2010 Constitution. The Constitution seeks to shift government from centralized to decentralized, and from "top-down" to "bottom-up". The Constitution and new legal framework place a strong emphasis on strengthening public participation. Strengthening public participation and governance is a core element in Kenya's strategy to accelerate growth and address long-standing inequalities in economic opportunities, investment, and service delivery in different parts of the country.